Pengaruh Imbangan Terigu, Tepung Garut (Maranta arundinacea L.) dan Tepung Wortel (Daucus carota L.) terhadap Karakteristik Kulit Pangsit Kukus - Hernawan, Aulia Azkia; Ningrumsari, Ida; Herlinawati, Lina (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2024)
The purpose of this study was to obtain the best results of the ratio of flour, arrowroot flour, and carrot flour to the characteristics of steamed dumpling skins. This research was conducted at the Chemistry Laboratory of the Faculty of Agriculture, Ma'soem University, Chemistry Laboratory at the Bakti Asih Bandung School of Analysis, Bandung Sibaweh Chemistry Laboratory from June to August 2023. This study used a randomized block design (RBD) with a total of 5 treatments, namely treatment A (70:30:0), treatment B (70:25:5), treatment C (70:20:10), treatment D (70:15 :15), and treatment E (70:10:20). The characteristic parameters observed were chemical parameters consisting of water content, carbohydrate content, and beta-carotene content, and sensory parameters were carried out by 25 panelists for the level of preference for color, aroma, taste, and elasticity. The results showed that the best treatment resulted from treatment D with a balance of 70 Wheat : 15 Garut Flour : 15 Carrot Flour which was produced from the effectiveness test. Steamed dumpling skin treatment D balance 70 Wheat : 15 Arrowroot Flour : 15 Carrot Flour with organoleptic values ??for color, aroma, firmness and taste respectively 3.36 (neutral), 3.08 (neutral), 3.48 ( neutral), 3.08 (neutral) and chemical content in the form of water content of 22.88%, carbohydrate content of 28.01% and beta carotene content after steaming of 0.15 mg.